Implementation of process technology and e-commerce in efforts to increase capacity and marketing of “Omah Kripik” - Muhammad Agus Sahbana; Achmad Setiawan; Zainol Arifin; Aan Jelli Priana; Maulana Abdul Rahman; Agus Nurwahid; Novriyan Isroq Nurman Syah Putra; Abdur Rozakh (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
Seloliman Village is one of the banana producers with an average production of 10-15 tons per year. The "Omah Kripik" business group was founded in 2022 to process bananas into banana chips. The process of making banana chips is still hampered by the problem of limited production capacity and product marketing with the potential for large availability of raw materials. This community partnership empowerment (PKM) activity aims to implement process technology and e-commerce to increase production capacity and product marketing.  Activity method: training and assistance in implementing process technology and e-commerce. The results obtained are the creation of an automatic banana slicer and marketing management training using e-commerce. The results of the PKM program activities were able to increase the production capacity of banana chips from previously only 20 kg a day to 60 kg a day. Additional knowledge about marketing management through e-commerce which is held is also able to attract the curiosity of Micro, Small and Medium Enterprises in Seloliman Village, Trawas District, Mojokerto Regency so that the products produced can have added economic value and be able to compete creatively. The impact of e-commerce is that it is able to increase sales from 100 packs per day to 300 packs per day through online orders.